Moufang Twin Trees and Z-systems : a step towards the classification of Moufang twin trees - Parr, Maximilian; Justus Liebig University Giessen (My University, 2021)
Based on the ideas presented in the paper `Moufang twin trees of prime order' by Matthias Grüninger, Max Horn, and Bernhard Mühlherr, we generalize their main result, that the unipotent horocyclic group of a Moufang twin tree of prime order is nilpotent of class at most two, to a considerably larger class of Moufang twin trees.
Keywords: Gruppentheorie; Gebäudetheorie; Zwillingsbäume; Moufang; ddc:510